2017
DOI: 10.1007/s10236-017-1061-4
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of zonal currents in the equatorial Indian Ocean: respective control of IOD and ENSO

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Although climate modes such as the Indian Ocean Dipole (IOD) are associated with zonal current variability in the Indian Ocean (Schott et al, 2009;Nagura and McPhaden, 2010;Sachidanandan et al, 2017), any effect on potential connectivity in our simulation is negligible compared to seasonality and stochastic variability.…”
Section: Seasonal Variabilitymentioning
confidence: 99%
“…Although climate modes such as the Indian Ocean Dipole (IOD) are associated with zonal current variability in the Indian Ocean (Schott et al, 2009;Nagura and McPhaden, 2010;Sachidanandan et al, 2017), any effect on potential connectivity in our simulation is negligible compared to seasonality and stochastic variability.…”
Section: Seasonal Variabilitymentioning
confidence: 99%
“…This transient feature of the EUC also determines the semiannual variations of zonal volume transport in the EIO, with the maximum eastward subsurface transport occurring in April and October (Nyadjro and McPhaden, 2014). The EUC shows a remarkable interannual variability and is significantly modulated by the Indian Ocean dipole (IOD) (Nagura and McPhaden, 2010;Zhang et al, 2014;Sachidanandan et al, 2017). Gnanaseelan and Deshpande (2018) showed that the enhancement and eastward extension of the EUC during strong IOD events could intensify and maintain the IOD through the intensification of oceanic responses.…”
Section: Introductionmentioning
confidence: 99%
“…In the IPWP, there are several major surface zonal currents, including the North Equatorial Countercurrent (NECC) (Chen et al., 2016; Kessler & Kleeman, 2000), Southwest Monsoon Current (SMC) (Schott et al., 2009), North Equatorial Current (NEC) (Chen & Wu, 2012; Qiu & Lukas, 1996) and South Equatorial Current (SEC) (Fine et al., 1994; Johnson et al., 2002). On seasonal and interannual time scales, ocean currents can be significantly influenced by ENSO, IOD, and Indian Ocean basin‐wide warming by modulating equatorial winds and oceanic internal variations (Nyadjro & McPhaden, 2014; Sachidanandan et al., 2017; Wang, 2019). The multiscale variabilities in these currents can lead to heat convergence/divergence in the IPWP, which not only likely feedbacks to the MISO over the Pacific Ocean (Lee et al., 2022; Yang et al., 2020) but also has profound implications for the climate and local environment.…”
Section: Introductionmentioning
confidence: 99%